Long-Term Efficacy, Safety, and Durability of Cabotegravir and Rilpivirine as 2-Drug Oral Maintenance Therapy After 6 Years of Study. (9th February 2022) - Sutton, Kenneth C; De Vente, Jerome; Leblanc, Roger; Dejesus, Edwin; Smith, Graham; Mills, Anthony; Baril, Jean-Guy; St. Clair, Marty; Stancil, Britt S; Vandermeulen, Kati; Spreen, William R
Abstract: Background: In the LATTE study, daily oral cabotegravir + rilpivirine demonstrated higher rates of efficacy than efavirenz + 2 nucleoside reverse-transcriptase inhibitors (NRTIs) through Week 96 in antiretroviral therapy (ART)-naive adults with human immunodeficiency virus (HIV)-1. We present the results from 6 years of continued treatment with oral cabotegravir + rilpivirine. Methods: LATTE was a phase IIb, randomized, multicenter, partially blinded, dose-ranging study in ART-naive adults with HIV-1. After a 24-week induction phase with cabotegravir + 2 NRTIs, participants with HIV-1 ribonucleic acid (RNA) <50 copies/mL were randomized to receive cabotegravir (10, 30, or 60 mg) + rilpivirine (25 mg) in the maintenance phase through Week 96 and switched to cabotegravir 30 mg + rilpivirine 25 mg in the open-label phase through Week 312. Results: Of 160 participants who entered the maintenance phase, 111 completed the study at Week 312. At Week 312, 105 (66%) participants maintained HIV-1 RNA <50 copies/mL, 15 (9%) had HIV-1 RNA ≥50 copies/mL, and 40 (25%) had no virologic data. Eight participants met protocol-defined virologic failure criteria through Week 312, 2 of whom met protocol-defined virologic failure criteria after Week 144. Six participants developed treatment-emergent resistance to 1 or both agents during the study, 3 of whom developed integrase inhibitor resistance substitutions. Two participants (1%) reported drug-related serious adverse events. Few adverse events led to withdrawal during the open-label phase (n = 5, 3%). Conclusions: Oral cabotegravir + rilpivirine demonstrated efficacy in the majority of participants and an acceptable safety profile through 6 years of treatment, demonstrating its durability as maintenance therapy for HIV-1. Abstract : Oral cabotegravir + rilpivirine maintained virologic suppression in the majority of participants and demonstrated an acceptable safety profile through 6 years of treatment, supporting its use as a flexible treatment strategy in people with HIV-1 receiving long-acting cabotegravir + rilpivirine.